A Cognitive Grammar Perspective on Temporal Conceptualization in SLA - Kermer, Franka (Studia Anglica Posnaniensia, 2020)
This article shows how cognitive grammar and cognitive linguistics theory offer a fruitful paradigm within which the process of second language acquisition can be examined. The aim is to describe and examine the benefit of using notions developed within the CG and CL frameworks to the study of crosslinguistic influence, especially conceptual transfer, in multilinguals. In recent years, the growth of empirical research concerning the contribution of cognitive-inspired theories to the study of second language acquisition and multilingualism has grown extensively. This article illustrates the possible contribution of CL to SLA by focusing on one particular line of inquiry: that of construal. Specifically, it examines how the notions developed within cognitive grammar theory can be useful tools for the analysis and comparison of conceptualization patterns of events, thus giving rise to transfer effects stemming from the way a person construes and conceptualizes events. The starting hypothesis is that conceptual transfer effects in the use of the target grammar, in this case the transfer effects in the TIME domain, may originate from the conceptualization patterns that the multilingual has acquired as a speaker of another L1. Previous transfer research has obtained evidence to suggest that patterns of L1 conceptualizations may be transferred into learners’ L2 through patterns that are similar to their L1. The utilization of central tools within cognitive grammar in order to unmask conceptual differences represents an important contribution to the state of the art of crosslinguistic influence research.